As good as one s word - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Handbook for preparing and writing research proposals By C P P Reid, IUFPRO-SPDC, 2000. 164 pp. ISBN 3 901347 23 2 US$ 25 E 26.60 US$ 5 E 5.30 for developing country scientists from IUFPRO member organisations. Cheque payable to IUFPRO-SPDC mu